Analisis Singkatan Dan Simbol Terhadap Formulir Discharge Summary Rawat Inap Untuk Penilaian Akreditasi Snars Mirm (12) Periode Februari Di Rumah Sakit Pusat Pertamina Jakarta Selatan - Livia Nuri Syafitri; Demiawan Rachmatta Putro Mudiono; Sustin Farlinda; Djasmanto Djasmanto (Indonesian Journal Publisher, 2022)
Recording in SNARS Edition 1 is included in the Hospital Management Standards group on Information and Record Management (MIRM), one of the medical standards in MIRM, namely the standardization of diagnosis codes, procedure/action codes, symbols, abbreviations, and their meanings contained in the MIRM 12 standard. Where in the assessment element, the hospital must have regulations on standardizing diagnosis codes, procedure/action codes, definitions, symbols used and which should not be used, abbreviations used and which should not be used, and monitored their implementation. Pertamina Central Hospital is a referral hospital and accredited B. Where this hospital becomes the Presidential Hospital. Medical Records used in the form of Electronic and Manual Medical Records. On the Medical Record Form in the application there are abbreviations and symbols. In the use of abbreviations and symbols, socialization has been carried out which contains a guideline entitled